Pyknodysostosis: A Case Report - H. Pakshir; H. Zarif Najafi (Tehran University of Medical Sciences, 2008)
Pyknodysostosis is a rare bone disease that has autosomal dominant trait. It is characterized by short stature, diffuse osteosclerosis, acro-osteolysis, finger, and nail abnormalities. Other features include open fontanelles and sutures, relative proptosis and obtuse mandibular gonial angle with relative mandibular prognathism. Intraoral features such as dental abnormalities also have been reported. In this report, a case of pyknodysostosis in a 9-year-old boy is presented. Most of the observed features were comparable to the other case reports but some findings such as repeated chest infection, sleep apnea, kyphosis, scoliosis, root shortness, pulp narrowing, supernumerary and hypodontia could not be observed in this case. Instead, in this patient features such as anterior open bite and decreased anterior tooth display, not reported in other cases, was evident.